Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
[tex]x^4-81=0 \\
(x^2)^2-9^2=0\\
(x^2-9)(x^2+9)=0\\
(x-3)(x+3)(x^2+9)=0\\
x=3 \vee x=-3[/tex]
so this is a difference of 2 perfect squares
so if
x^2-y^2 then it is equal to (x-y)(x+y)
so
x^4-81=[(x^2)^2]-[(9)^2]=(x^2-9)(x^2+9)
so we know if xy=0 then x or/and y=0 so assume that they are equal to zero
x^2+9=0
we can't do anything about this because
x^2=-9
and that is not possible in the real realm
x^2-9=0
yet another difference of 2 perfect squares
x^2-3^2=(x-3)(x+3)=0
set them to zero
x-3=0
x=3
x+3=0
x=-3
so x=3 or -3
so if
x^2-y^2 then it is equal to (x-y)(x+y)
so
x^4-81=[(x^2)^2]-[(9)^2]=(x^2-9)(x^2+9)
so we know if xy=0 then x or/and y=0 so assume that they are equal to zero
x^2+9=0
we can't do anything about this because
x^2=-9
and that is not possible in the real realm
x^2-9=0
yet another difference of 2 perfect squares
x^2-3^2=(x-3)(x+3)=0
set them to zero
x-3=0
x=3
x+3=0
x=-3
so x=3 or -3
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.